Telecommunications Industry in India: Growth Performance and Opportunities Ahead - Sudan, Falendra K. (Economic Journal of Development Issues, 2010)
The Indian telecommunications industry is growing at the fastest pace in the world, which has made it a key contributor to India’s economic development. Since India’s telecom sector trails that of other Asian economies by around 10 years, growth is a certainty. India is currently the third-largest mobile market in the world in terms of mobile subscribers. The Indian telecom market generated revenues of approximately US$ 20 billion in 2006-07. Further, the industry is expected to register a compound annual growth rate of approximately 21 per cent from 2006-07 to 2009-10 and scale US$ 43 billion by 2010. It is, thus, not surprising that several foreign companies are making large investments in India. Not to be left behind, Indian cellular operators have also proposed investments worth US$ 14.78 billion in 2007-08 to fuel their massive investment plans. Even though the Indian telecommunications industry has crossed a subscriber base of 233 million, its tele-density is about 20 per cent. Thus, the Indian market provides telecom service providers with a large untapped potential, given the country’s increasing population and its low tele-density. The Government has plans to raise tele-density to 40-45 per cent by 2010, thereby offering greater growth opportunities for service providers. The fact that the Indian telecommunications industry witnesses an addition of approximately 6.4 million subscribers every month is proof of the country’s immense growth potential. Thus, there exists enormous business potential for telecommunications industry on account of the country’s low tele-density. No doubt, there has been a revolutionary shift in telecom growth in India in the last decade, several lacunae persist and need sustained policy attention to achieve a just distribution of telecommunications resources. Key words: Telecommunication; India; Growth performance; Opportunities Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 21-33